PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJADAN STRES KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan Bagian Unit Kartu Kredit Bank X Regional Surabaya) - Dwi Ratmawati; Arfandi D Nugroho (Politeknik Negeri Lhokseumawe, 2021)
Abstract: One of sector that has important role in supporting economic development is the banking. And one of the banking product is credit cards are optionally. In improving its performance needs to be supported by good employee performance. But, the performance of emloyees in the Bank X Credit Card Unit still hasn’t reached the target. The objectives of this research is to identify the effect of emotional intelligence on job performance with job satisfaction and job stress as intervening variabel at Bank X Credit Card Unit. The method used in this research is quantitative research with the total number of respondents as much as 50 employees of the Bank X Credit Card Unit . The data is analized with smart PLS and the results of this research shows that emotional intelligence has positive and significant effect on job performance, emotional intelligence has a negative and significant effect on job stress, emotional intelligence has a positive and significant effect on job performance, job satisfaction hasn’t positive and significant effect on job performance and job stress has negative and significant effect on job performaceKeyword : Emotional Intelligence, Job Performance, Job Stress, Job Satisfaction, Banking